THE ANALYSIS OF THE CHANGES IN THE INTERIOR DESIGN OF HOUSES DUE TO THE WESTERNIZATION MOVEMENTS IN 19th CENTURY IN THE OTTOMAN EMPIRE - Polat, Orhun (Advances in Social Sciences Research Journal, 2018)
Westernization movements during the 19th century caused great changes in interior design of Ottoman houses. It is a question of debate whether the cited changes have been carried forward to our day. The interior design features of traditional Ottoman houses prior to Westernization period were analyzed as methodology primarily in order to answer this question discussed within the purview of the study. Subsequently, the interior design features of the Ottoman house influenced through the 19th century Westernization movements and the interior design features of the 21st century Turkish houses were determined. At the next stage, interior designs of houses belonging to these three phases were compared in terms of spatial organizations, usage of furniture and design styles. At the last stage of the study, it was determined if the changes caused through the 19th century Westernization movements in the interior design of the Ottoman house were preserved in the 21st century Turkish houses in line with the results obtained from the comparisons made to this end.